Plasmin(ogen) at the Nexus of Fibrinolysis, Inflammation, and Complement - Foley, Jonathan H. (Seminars in Thrombosis and Hemostasis, 2017)
The diverse mechanisms by which the plasmin(ogen) system is involved in human physiology and pathology are constantly being delineated. For many years, the plasmin(ogen) system was chiefly known as the system responsible for vascular fibrinolysis. Although this is an important function of the plasmin(ogen) system, we now recognize that plasmin(ogen) is critically important as a mediator of inflammation and the innate immune system, which impacts upon a diverse set of mechanisms underlying the pathologies of many diseases. The current review focuses on recent developments in plasmin(ogen) system activation and regulation and how dysregulation of this finely tuned system may contribute to inflammatory disease (atherosclerosis), impaired wound healing, and infection.
Keywords: fibrinolysis; plasminogen receptors; inflammation; complement; wound healing